Praanggapan dan Entailmen dalam Pemrosesan Bahasa Dialog Al-Qur’an: Tinjauan Pragmatik dan Psikolinguistik - Shabri, Irsyad; Aulia, Rahmadianti; Yanti, Rahma; ., Yalmiadi (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
The study of presupposition and entailment in Qur’anic dialogue has significant academic relevance, as both aspects contribute to the construction of implicit meaning, cognitive structures, and pragmatic comprehension of religious texts. The dialogue between Prophet Moses and Khidr in Surah Al-Kahf (verses 66–82) represents a complex linguistic interaction enriched with theological, ethical, and educational dimensions, thus requiring in-depth analysis from pragmatic and psycholinguistic perspectives. This study aims to describe the forms, functions, and roles of presupposition and entailment in language processing within the Moses–Khidr dialogue and to reveal their cognitive and educational implications. This research adopts a qualitative descriptive approach. The data consist of utterances in the dialogue between Moses and Khidr, collected through non-participant observation and systematic note-taking. The primary data source is the Qur’an, while secondary sources include classical Qur’anic exegesis, hadith, and relevant works on pragmatics and psycholinguistics. Data analysis is conducted using the pragmatic identity method with the Determinant Element Sorting Technique (Pilah Unsur Penentu) through stages of identification, classification, interpretation, and synthesis. The findings indicate that presupposition and entailment function as integrated linguistic-cognitive mechanisms in constructing multidimensional meaning. Presupposition reflects implicit assumptions concerning divine authority, obedience, and human limitation, whereas entailment represents the logical consequences of utterances and actions. From a psycholinguistic perspective, these mechanisms activate inferential processing, semantic integration, and emotional regulation. The study concludes that the Moses–Khidr dialogue is educationally transformative, emphasizing the values of patience, humility, and epistemic awareness in learning and interpreting sacred texts.